Enhanced stability of G-quadruplexes from conformationally constrained aep-PNA backbone - Sharma, Nagendra K.; Ganesh, Krishna N. (Organic & Biomolecular Chemistry, 2011)
Nucleic (DNA) acids having contiguous stretch of G sequence form quadruplex structure, which is very critical to control cell division. Recently the existence of G-quadruplex in RNA is also reported in presence of monovalent metal ion. PNA is a promising DNA analogue which binds strongly to DNA to form PNA: DNA duplex or PNA(2) : DNA triplex. PNA also forms quadruplexes such G-quadruplex and i-motif in G and C-rich sequences respectively. aep-PNA containing a prolyl ring is one of several PNA analogues that provide rigidity and chirality in backbone and has binding affinity to natural DNA which is higher than that of PNA. Here we examine the ability of aep-PNA-G to form a quadruplex by UV, CD and mass spectroscopic techniques.